Efficacy of inactivated Avian Pathogenic Escherichia coli against the bacterial infections in broiler chickens - Yong, Wendy Wai Kheng (2016)
Avian Pathogenic Escherichia coli (APEC) causes colibacillosis in poultry, which it manifests various clinical conditions such as colisepticemia and cellulitis. This objective of this study was to determine efficacy of inactivated APEC either as single or combination with virulent associated gene (VAG) 5 and 6 against the bacterial infection in broiler chickens. Eighty-four day-old broiler chickens were equally divided into seven groups. On day 1, groups 1 and 4 were inoculated subcutaneously with inactivated APEC with VAG 5. Groups 2 and 5 with VAG 6 and groups 3 and 6 with combination of VAG 5 and VAG 6. Group 7 was not inoculated as it was acted as control group. On day 14, booster was given to groups 4, 5 and 6. On day 28, the chickens in each group were divided into the challenge and non-challenge groups. Chickens in the challenge groups were inoculated (0.1 mL) with VAG6 (108 cfu/mL) either via intramuscular or intranasal routes. On day 35, all the chickens were sacrificed. The livers and spleens were collected for bacterial identification, while livers and trachea for histopathology. The study showed that two chickens from the control group were stunted growth, dehydrated and inappetence after challenged intramuscularly, and showed gross lesions of perihepatitis and pericarditis.E. coli was isolated from only one sample of the same group.Histologically, severe hepatitis with severe necrosis and degeneration of the hepatocytes, and severe tracheitis with severe necrosis and degeneration were recorded. In contrast, mild lesions of hepatitis with mild necrosis and degeneration of hepatocytes, and mild tracheitis with mild necrosis and degeneration were recorded in groups of chickens without clinical signs.Based on the clinical signs, lesions and bacterial culture, the inactivated APEC either as single or combination with VAG 5 and 6 gives better protection against the bacterial infection in broiler chickens compared to non-inoculated group. In conclusion, inactivated APEC either as single or combination with VAG 5 and 6 was effective and could provide protection against VAG 6 challenged.